Percurso formativo e profissional de docentes licenciados em Matemática pelo Instituto Federal de Educação, Ciência e Tecnologia do Tocantins – IFTO - Lopes, Kênya Maria Vieira (2022)
The Federal Institute of Education, Science and Technology of Tocantins (IFTO) trained, in a decade, professionals in the degree courses in Performing Arts, Computing, Biological Sciences, Physical Education, Physics, Mathematics, Portuguese Language and Chemistry. In view of this context, the following problem was delimited: in what way did initial training contribute (or not) to the professional performance of teachers graduated in Mathematics from the IFTO? The objective was to analyze the training and professional path of teachers graduated in Mathematics by IFTO in the first decade of the institution (2008 to 2018). The theoretical contributions followed the axes: (i) 'initial training', with Garcia, Gatti, Nóvoa, Imbernón, D'Ambrosio, Shulman, Skovsmove; (ii) 'teaching profession, career and professionalization', with Contreras, Diniz-Pereira, Gentili, Imbernón, Nóvoa, Pimenta and Ghedin, Tardif and Lesard; (iii) ‘training for new challenges’, with Chassot, D’Ambrosio, De Masi, Morin, Skovsmove, among others. The research is qualitative in nature, with a methodological assumption based on Bardin, Bicudo and Franco. It is classified, from the point of view of its purpose, as basic and strategic. As for its objectives, it is descriptive-exploratory and interpretive. The data production procedures consisted of document analysis, application and analysis of a questionnaire and interview. In the first stage of the research (2019 to 2021/1), 229 graduates (out of 413 graduates) from the 11 IFTO degree courses participated. The graduates answered a questionnaire via Google Forms to characterize the subjects. In the second (2021/1 to 2022), 20 teachers graduated from Mathematics courses (Paraíso do Tocantins and Palmas campuses) participated in interviews with the researcher via Google Meet. As for the contributions of initial training to the performance of Mathematics teachers, the following analytical categories were generated: teachers' contributions (personal and professional); of the disciplines; extracurricular activities and PIBID. It is concluded that initial training has significantly contributed to the professional performance of graduates, such as remote teaching in times of a pandemic. This allowed teachers to proactively position themselves in the face of the challenges presented. Among these challenges we can mention: acceptance of the 'new normal' and living with uncertainties; adaptation to teleworking; dealing with the disruption of time and space; the adaptations/changes in the didactic strategies of the classes; the relationship with socio-emotional issues and; overcoming/confronting problems arising from the pandemic period. Such findings collaborate with the assertion that initial training courses can prepare teachers for both traditional and new challenges. However, they are not (and cannot be) those courses that are considered sufficient for teachers, requiring continued improvement. Thus, it is up to teachers to recognize their incompleteness and then seek renewals and transformations through personal and professional learning, these resulting from pedagogical praxis - which constitutes one of the challenging training fields for the educator, as evidenced in this research.